The Devil is a part-timer! [videorecording (DVD)] - Wagahara, Satoshi (FUNimation Productions, 2014)
"When Satan is run out of his infernal kingdom, he finds himself virtually powerless in modern-day Tokyo. ... As Satan flips burgers and tries to regain his evil magic, he's pestered by a righteous hero who tracked him to Earth, a video-game-loving fallen angel looking for a way back into heaven, and the most unholy of enemies: a rival fast food franchise"--Container.